Diminished ovarian reserve is associated to euploidy rate: a single center study - Carnesi, Edoardo; Castellano, Stefano; Albani, Elena; Busnelli, Andrea; Smeraldi, Antonella; Bulbul, Ozgur; Morenghi, Emanuela; Immediata, Valentina; Levi-Setti, Paolo Emanuele (Frontiers in Endocrinology, 2025)
BackgroundReproductive success shows a well-documented decline with advancing maternal age, primarily due to chromosomal abnormalities (aneuploidies) in embryos. While ovarian reserve markers such as Anti-Müllerian Hormone (AMH) and Antral Follicle Count (AFC) traditionally serve as quantitative predictors of fertility, emerging evidence suggests they may also reflect oocyte quality, particularly in patients with Diminished Ovarian Reserve (DOR). The relationship between these biomarkers and embryo chromosomal status remains complex and poorly understood.MethodsWe conducted a retrospective analysis of in vitro fertilization (IVF) cycles performed between 2015 and 2022, involving 773 female patients who underwent IVF and pre-implantation genetic screening for aneuploidy (PGT-A). Our patient cohort was divided into two groups: Group 1, consisting of women who achieved at least one euploid embryo, and Group 2, comprising women who did not.ResultsThe main outcome measures included the rate and number of euploid blastocysts and their correlation with ovarian reserve. Our results showed a statistically significant association between independent variables and embryo ploidy: AMH levels (OR 1.09; 95% CI 1.04-1.14, p<0.001), the age of the woman (OR 0.82; 95% CI 0.79-0.85, p<0.001), the number of oocytes retrieved (OR 1.050; 95% CI 1.01-1.08, p=0.05), and the fertilization rate (OR 6.69; 95% CI 2.67-16.77, p<0.001).ConclusionOur findings suggest that AMH levels are associated with embryo ploidy rate. These insights could enhance counseling practices in assisted reproductive technology (ART), offering patients a more detailed understanding of their infertility prognosis and the factors influencing IVF outcomes.